Enhancing Training Effectiveness: Exploring the Impact of Participant Motivation at a Workforce Training Center in Pekanbaru, Indonesia - Desvi Emti (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to determine the level of effectiveness of workforce training and the motivation of its participants, as well as to assess the influence of participants' motivation on the training effectiveness at the Workforce Training Center in Pekanbaru City. The sample was selected using a proportional random sampling technique, comprising 104 respondents who participated in the training program at the Workforce Training Center. The data were analyzed using a descriptive method, and a quantitative approach with a simple linear regression equation was employed to measure the influence of the studied variables. The results indicate that participants' motivation at the training center generally falls below the good category. This is attributed to the participants' lack of awareness of the need for personal achievement in their lives, often relying on their parents for responsibility. Notably, participants from outside Pekanbaru exhibit better learning motivation. Additionally, the training effectiveness is also not rated as good, as evidenced by the participants' limited positive reactions during the program, resulting in unachieved behavioral changes and training goals. Hypothesis testing confirms that participants' motivation significantly influences training effectiveness at the Workforce Training Center.